2018
DOI: 10.1186/s10152-018-0513-7
|View full text |Cite
|
Sign up to set email alerts
|

First record of the non-indigenous jellyfish Blackfordia virginica (Mayer, 1910) in the Baltic Sea

Abstract: Marine invasions are of increasing concern for biodiversity conservation worldwide. Gelatinous macrozooplankton contain members, which have become globally invasive, for example the ctenophore Mnemiopsis leidyi or the hydromedusae Blackfordia virginica. B. virginica is characterised by a large salinity tolerance, with a brackish-water habitat preference, and by a metagenic life history strategy with an alternation between sexually reproducing planktonic medusae and asexually reproducing benthic polyps to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Here, evolutionarily ancient organisms, which are located at the base of the metazoan tree of life, are expected to provide important insight into host–microbe interactions. Two basal metazoan species, which are widely distributed in marine environments, partly due to their large adaptability (Dawson & Jacobs, 2001; Jaspers, Huwer, Weiland‐Bräuer, & Clemmesen, 2018), are the moon jellyfish Aurelia aurita and the comb jelly Mnemiopsis leidyi (Figure 1a). Their ecological impacts are widely recognized (Bayha & Graham, 2014; Jaspers, Huwer, Antajan, et al, 2018), but the characterization of their associated microbial communities and interactions lacks behind; however, the relatively simple morphology with only two tissue layers as surfaces for microbial colonization definitely allows for such studies.…”
Section: Introductionmentioning
confidence: 99%
“…Here, evolutionarily ancient organisms, which are located at the base of the metazoan tree of life, are expected to provide important insight into host–microbe interactions. Two basal metazoan species, which are widely distributed in marine environments, partly due to their large adaptability (Dawson & Jacobs, 2001; Jaspers, Huwer, Weiland‐Bräuer, & Clemmesen, 2018), are the moon jellyfish Aurelia aurita and the comb jelly Mnemiopsis leidyi (Figure 1a). Their ecological impacts are widely recognized (Bayha & Graham, 2014; Jaspers, Huwer, Antajan, et al, 2018), but the characterization of their associated microbial communities and interactions lacks behind; however, the relatively simple morphology with only two tissue layers as surfaces for microbial colonization definitely allows for such studies.…”
Section: Introductionmentioning
confidence: 99%
“…Denayer (1973) also described that the pigment was easily degraded in fixatives. In addition, Jaspers et al (2018) observed grey pigmentation in live individuals of B. virginica from the Baltic Sea. Furthermore, Bouillon et al (1988) recorded Blackfordia sp.…”
Section: Discussionmentioning
confidence: 93%
“…Blackfordia virginica sensu lato has been found in brackish waters from various areas from tropical to subarctic (e.g. Genzano et al 2006, Bardi & Marques 2009, Chícharo et al 2009, Freire et al 2014, Faasse & Melchers 2014, Toyokawa & Fujii 2015, Jaspers et al 2018. It has attracted a large amount of scientific interest due to its known invasion history world-wide (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite very high densities of the recently established non-indigenous hydromedusa Blackfordia virginica in Kiel Canal (Jaspers et al 2018), so far no studies have yet assessed its impact on zoo-and ichthyoplankton communities.…”
Section: Jellyfish Predation On Mesozooplanktonmentioning
confidence: 99%
“…Müller, 1776), sea gooseberry Pleurobrachia pileus (O.F. Müller, 1776) and the non-indigenous sea walnut Mnemiopsis leidyi (A. Agassiz, 1865) (Javidpour et al 2006)) and at least seven species of hydromedusa, including Sarsia tubulosa (M. Sars, 1835), Aequorea vitrina Gosse, 1853, Obelia spp., Rathkea octopunctata (M. Sars, 1835), Phialidium hemisphaericum (Linnaeus, 1767) (Allwein 1968), Lizzia blondina Forbes, 1848, as well as the non-indigenous species Maeotias marginata (Modeer, 1791) (Väinölä et al 2001) and Blackfordia virginica Mayer, 1910 (Jaspers et al 2018). At the same time, jellyfish blooms in the Baltic Sea are common and oftentimes reach very high biomasses (Olesen et al 1994;Schneider and Behrends 1998;Goldstein and Riisgård 2016).…”
Section: Introductionmentioning
confidence: 99%